Role of NTFPs in Economic Empowerment of Rural Women - Paloti, Lakshmi M.; Hiremath, Uma S. (Indian Forester, 2005)
This study shows that NTFPs playa significant role in the livelihood of forest dwellers. Totally 9 NTFPs namely leaves for meal plates, edible gum, fruits, fuel wood, Pongamia seeds, materials for basket and brooms are being collected, processed and marketed by the rural women and help to supplement their family income during off-season. Rural women account for more of the households time spent in collection and processing of NTFPs.